Land cover changes assessment using object‐based image analysis in the Binah River watershed (Togo and Benin). Issue 10 (26th October 2015) - Badjana, Hèou Maléki; Helmschrot, Jörg; Selsam, Peter; Wala, Kpérkouma; Flügel, Wolfgang‐Albert; Afouda, Abel; Akpagana, Koffi
Abstract: In this study, land cover changes between 1972 and 2013 were investigated in the Binah River watershed (North of Togo and Benin) using remote sensing and geographic information system technologies. Multitemporal satellite images—Landsat MSS (1972), TM (1987), and OLI‐TIRS (2013)—were processed using object‐based image analysis and post–classification comparison methods including landscape metrics and changes trajectories analysis. Land cover maps referring to five main land cover classes, namely, agricultural land, forest land, savannah, settlements, and water bodies, were produced for each acquisition date. The overall accuracies were 76.64% (1972), 83.52% (1987), and 88.84% (2013) with respective Kappa statistics of 0.69, 0.78, and 0.86. The assessment of the spatiotemporal pattern of land cover changes indicates that savannah, the main vegetation type, has undergone the most dominant change, decreasing from 67% of the basin area in 1972 to 56% in 1987 and 33% in 2013. At the same time, agricultural land has significantly increased from 15% in 1972 to 24% in 1987 and 43% in 2013, while some proportions of agricultural land were converted to savannah relating to fallow agriculture. In total, more than 55% of the landscape experienced changes between 1972 and 2013. These changes are primarily due to human activities and population growth. In addition, agricultural activities significantly contributed to the increase in the number of patches, degree of division, and splitting index of forest and savannah vegetations and the decrease in their effective mesh sizes. These results indicate further fragmentation of forest and savannah vegetations between 1972 and 2013. Further research is needed to quantitatively evaluate the influences of individual factors of human activities and to separate these from the impacts of climate change‐driven disturbances. Key Points: Land cover changes are assessed using remote sensing and GIS techniques Changes in landscape structure over time are characterized for a West African basin